2016
DOI: 10.1007/s10709-016-9932-z
|View full text |Cite
|
Sign up to set email alerts
|

Genome wide association study (GWAS) for grain yield in rice cultivated under water deficit

Abstract: The identification of rice drought tolerant materials is crucial for the development of best performing cultivars for the upland cultivation system. This study aimed to identify markers and candidate genes associated with drought tolerance by Genome Wide Association Study analysis, in order to develop tools for use in rice breeding programs. This analysis was made with 175 upland rice accessions (Oryza sativa), evaluated in experiments with and without water restriction, and 150,325 SNPs. Thirteen SNP markers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 48 publications
0
36
0
1
Order By: Relevance
“…In this sense, the marker associated with this region of the genome may be useful for the production of hybrids resistant to water stress. In fact, this notion is the hypothesis of several GWAS for grain yield (Ain et al., ; Ma et al., ; Pantalião et al., ; Sukumaran et al., ; Zhang et al., ). These authors claim the importance of applying GWAS for grain yield and its related traits to incorporate genes tolerant to environmental stress.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In this sense, the marker associated with this region of the genome may be useful for the production of hybrids resistant to water stress. In fact, this notion is the hypothesis of several GWAS for grain yield (Ain et al., ; Ma et al., ; Pantalião et al., ; Sukumaran et al., ; Zhang et al., ). These authors claim the importance of applying GWAS for grain yield and its related traits to incorporate genes tolerant to environmental stress.…”
Section: Discussionmentioning
confidence: 95%
“…In fact, this notion is the hypothesis of several GWAS for grain yield (Ain et al, 2015;Ma et al, 2016;Pantalião et al, 2016;Sukumaran et al, 2015;Zhang et al, 2017). These authors claim the importance of applying GWAS for grain yield and its related traits to incorporate genes tolerant to environmental stress.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…In upland rice, genetic variation for drought tolerance is available in gene banks (Pantalião et al, 2016), and the useful variability must be better exploited in order to be incorporated into the breeding programs. (Serraj et al, 2011;Kumar et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Genes related to drought tolerance in rice have recently been obtained via mapping of QTLs (Dixit et al, 2014) and association mapping (Pantalião et al, 2016) by means of single nucleotide polymorphism (SNP) markers, functional genomics, microarrays (Parida et al, 2012;Borah et al, 2017), RNA-Seq (Huang et al, 2014;Silveira et al, 2015) or simply by using candidate genes homologous to those identified in other species (Shaar-Moshe et al, 2015;Abreu et al, 2016). The cost of high-resolution genotyping, as well as sequencing, has fallen year by year, which has opened the possibility of identifying genes related to drought tolerance via wholegenome resequencing (Jain et al, 2014).…”
Section: Introductionmentioning
confidence: 99%